Effect of Environmental Noise and Social Environment on Quality Life of Workers at Weaving Department - Yulianto, Budi; Murti, Bhisma; Hartono, Hartono; Masykuri, Muhammad; Saadah, Nurlailis (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Noise exposure with high intensity on working environment during long time exposure could induce physic  and physicologycally  disorder, giving feeling of uncomfortable and would affect stress and worker quality of life. In other side, social environment at working places that consist of social capital, family support, and good style of leadership phsyicologically giving feeling of comfortable and would reduce phsycologycal burden of workers. Aim of this study was to knew effect  of environmental noise and social environment simultaneously toward quality life of workers. This study was conducted on workers of PT Kusumahadi Santosa, Karanganyar Regency, Central Java Province, Indonesia. Samples were 250 workers, selected by simple random sampling method.  Exogenous variable consist of environmental noise, social capital, family support, leadership style, workers status and age. Endogenous variable on this study was quality of life. Data from all variables collected by using questionnaire and analyse with Path Analysis. Result of this study showed that environmental noise on weaving department affect quality of life by stress. Good social capital on working places affect quality of  life of workers. Good works  support  affect quality life of workers.